The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

A double-blind, randomized, placebo-controlled test of the effects of cannabidiol on fear elicited by a 10% carbon dioxide-enriched air breathing challenge - Ellen W. Leen-Feldner; Teah-Marie Bynion; Graham M. L. Eglit; Marcel O. Bonn-Miller; L. Riley Gournay; Matthew T. Feldner (Psychopharmacology, 2025)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Interplay of egg white gel pH and intragastric pH: Impact on breakdown kinetics and mass transport processes - Alisha Kar; Alex G. Olenskyj; Maria Garcia Guerrero; Riley Graham; Gail M. Bornhorst (Food Research International, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Inferring infection hazard in wildlife populations by linking data across individual and population scales - Kim M. Pepin; Shannon L. Kay; Ben D. Golas; Susan S. Shriner; Amy T. Gilbert; Ryan S. Miller; Andrea L. Graham; Steven Riley; Paul C. Cross; Michael D. Samuel; Mevin B. Hooten; Jennifer A. Hoeting; et al. (Ecology Letters, 2017)
Our ability to infer unobservable disease‐dynamic processes such as force of infection (infection hazard for susceptible hosts) has transformed our understanding of disease transmission mechanisms and capacity to predict disease dynamics. Conventional methods for inferring FOI estimate a time‐averaged value and are based on population‐level processes. Because many pathogens exhibit epidemic cycling and FOI is the result of processes acting across the scales of individuals and populations, a flexible framework that extends to epidemic dynamics and links within‐host processes to FOI is needed. Specifically, within‐host antibody kinetics in wildlife hosts can be short‐lived and produce patterns that are repeatable across individuals, suggesting individual‐level antibody concentrations could be used to infer time since infection and hence FOI . Using simulations and case studies (influenza A in lesser snow geese and Yersinia pestis in coyotes), we argue that with careful experimental and surveillance design, the population‐level FOI signal can be recovered from individual‐level antibody kinetics, despite substantial individual‐level variation. In addition to improving inference, the cross‐scale quantitative antibody approach we describe can reveal insights into drivers of individual‐based variation in disease response, and the role of poorly understood processes such as secondary infections, in population‐level dynamics of disease.

Geographically disjunct populations and widespread genets in an endangered halophilic plant, the Amargosa niterwort (Nitrophila mohavensis) - Andrew P. Martin; Elizabeth Paulson; Riley Graham (Conservation Genetics, 2013)

Does lycopene offer human LDL any protection against myeloperoxidase activity? - Poh Yeong Chew; Lucy Riley; Daniel L. Graham; Khalid Rahman; Gordon M. Lowe (Molecular and Cellular Biochemistry, 2012)

Central effects of urotensin-II following ICV administration in rats - Jane Gartlon; Frederick Parker; David Harrison; Stephen Douglas; Tracey Ashmeade; Graham Riley; Zoe Hughes; Stephen Taylor; Richard Munton; Jim Hagan; Jackie Hunter; Declan Jones (Psychopharmacology, 2001)

Evidence that orexin-A-evoked grooming in the rat is mediated by orexin-1 (OX 1 ) receptors, with downstream 5-HT 2C receptor involvement - Mark S. Duxon; Jennifer Stretton; Kathryn Starr; Declan N.C. Jones; Vicky Holland; Graham Riley; Jeff Jerman; Stephen Brough; Darren Smart; Amanda Johns; Wai Chan; Rod A. Porter; et al. (Psychopharmacology, 2001)